“Satu Nagari Satu Event” Sebuah Upaya Untuk Kemajuan Kabupaten Tanah Datar - Feby Hidayat; Aldri Frinaldi; Lince Magriasti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
The authority given to local governments by the central government to manage regional affairs for the benefit of the people is known as decentralization. The Tanah Datar Regency Government makes a policy through the “One Village One Event” program. The purpose of this study was to determine the benefits and inhibiting factors in implementing “One Village One Event” using a qualitative approach. By describing the implementation of “One Village One Event” activities, this type of research is descriptive in nature. In this study, interview techniques, documentation, literature reviews in journals and online media, and documentation were used to collect data. The results of this study indicate that the benefits of ”One Village One Event” are Preserving Culture, Exploring Local Potential, Increasing Tourism and Increasing the Community's Economy. The implementation went smoothly and without any significant obstacles.